(untitled) (Bangladesh Journal of Psychology, 2025)
Psychological resilience is one of the most important areas of study in positive psychology. A lot of research has been done on this construct in the Bengali population. Most research to measure the resilience of the Bangladeshi population has been conducted using a translated resilience scale. Although very few studies have been conducted examining the psychometric properties of the Bangla Resilience Evaluation Scale in Bangladeshi culture, they are not at all extensive. Therefore, the present study aimed to validate the Bangla Resilience Evaluation Scale (BRES) with comprehensive psychometric properties. This study was conducted through a cross-sectional survey design, which included 786 Bangladeshi adults aged 18 to 64 years. Exploratory factor analysis (EFA) considering sub-sample-1 (n = 400) revealed a single-factor structure for the BRES, which explained 62.53% of the total variance. The fit indices for the BRES obtained through confirmatory factor analysis (CFA) on subsample-2 (n=386) were found to be good (χ2/df=3.07, GFI=.967, CFI=.964, SRMR=.042, and RMSEA=.073). The single-factor structure of the BRES was similar to the Chinese version. Good internal consistency reliability (α=.874, ꞷ=.875), and both convergent and discriminant validity were established in the BRES through various statistical analyses. Thus, the one-factor BRES can be used as a valid and reliable measure to assess the psychological resilience of the Bangladeshi population. Bangladesh Journal of Psychology, Vol. 25, December 2025, pp. 50-67